Human Capital and Economic Complexity in Iran - Hoda Zobeiri; mani motameni (پژوهشهای اقتصادی, 2020)
Economic complexity reflects the capabilities of a country and determines the level of economic growth and development. Investing in knowledge and human capital due to increasing the capabilities of economic actors is essential to achieve a complex economy. This paper examines the relationship between human capital and economic complexity in Iran during 1971-2017. Empirical analysis shows that primary school enrollment has no significant correlation to economic complexity. In addition, R&D expenditure as percentage of GDP has no significant relation to economic complexity. According to Johansen-Juselius co-integration test there is no co-integrating relationship between the variables under study. However, government expenditure on tertiary education as percentage of GDP, shown by TR, is co-integrated with economic complexity. Based on Granger causality test, there is a unidirectional causality from TR to economic complexity. Impulse response analysis indicates that economic complexity responses to TR after three years. If spending on higher education increases by 10 percent, the economic complexity index will increase by 11 percent.